2022
DOI: 10.3390/brainsci12091171
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Modulation in Children with Developmental Coordination Disorder Compared to Autism Spectrum Disorder and Typically Developing Children

Abstract: Developmental Coordination Disorder (DCD) is one of the least studied and understood developmental disorders. One area that has been minimally investigated in DCD is potential issues with sensory modulation. Further, in other neurodevelopmental disorders (e.g., autism spectrum disorder (ASD)) sensory modulation is related to many other challenges (e.g., social issues, repetitive behaviors, anxiety); however, such potential relationships in children with DCD have been largely unexplored. The purpose of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 149 publications
0
1
0
Order By: Relevance
“…In sum, we could not confirm our prediction that children with DCD show atypical feedback control. Nevertheless, the atypical sensory processing (Elbasan et al, 2012; Ringold et al, 2022; Schoemaker et al, 2001) observed in children with DCD could be a factor affecting feedback control.…”
Section: Discussionmentioning
confidence: 99%
“…In sum, we could not confirm our prediction that children with DCD show atypical feedback control. Nevertheless, the atypical sensory processing (Elbasan et al, 2012; Ringold et al, 2022; Schoemaker et al, 2001) observed in children with DCD could be a factor affecting feedback control.…”
Section: Discussionmentioning
confidence: 99%